(Vitamin E from Palm Oil its Nutritional Properties) - Sudibyo, Agus (Warta Industri Hasil Pertanian, 1996)
Vitamin E can be derived from palm oil as a mixture of alpha tocopherol and tococtrienols.As a minor components,vitamin E have traditionally been the most interesting.It does not only posses antioxidant properties which is important for enhancing the stability of the oil against oxidation but also possess physiological properties that are presentlygaining much prominence in biomedical applications.Some studies indicated that tocotrienols were more efficient than tocopherol in terms of hypocholesterolemic,anti-cancer and antioxidant properties.This artcle reviews characterization and production of vitamin component,nutrional properties,and potential applications of vitamin E from palm oil in the food and pharmaceutical industries.